Art, Therapy, and Design. (2nd January 2018) - Graham, Gordon
Abstract: This paper first elaborates 'Art' and the aesthetic as these concepts emerged in the eighteenth century, and uncovers the conflict between the resulting ideal of 'art for art's sake' and the increasing use 'art therapy' for personal and social purposes. Taking this conflict to be a reason for the rejection of 'Art', it considers two accounts of 'the end of Art', one by Arthur Danto and the other by Nicholas Wolterstorff. The paper argues that both accounts fall short of adequately recognizing the presence of the aesthetic in everyday life, and that once we do acknowledge the properly aesthetic character of 'Design', a way of thinking is opened up that can make better sense of art therapy. The paper concludes with a brief indication of where the next philosophical question about art therapy lies.